2001
DOI: 10.1103/physrevb.63.165327
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of charge density waves by surface nanostructures onTaS2

Abstract: The transition metal dichalcogenide 1T-TaS 2 forms charge density waves due to the quasi-twodimensionality of its electronic structure. Here we show how the growth of Rb nanowires on the surface of 1T-TaS 2 affects the superstructure of the charge density waves. Scanning tunneling microscopy and lowenergy electron diffraction studies show the replacement of the normal TaS 2 room temperature ͱ13ϫͱ13 phase by c(2ͱ3ϫ4)rect. and 3ϫ3 superstructures depending on the state of nanowire growth. Furthermore, angle reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…An alternative route to modify the CDW structure is intercalation that can change the electronic structure and induce strain. 1T-TaS2 is a case in point, as a new rectangular 𝑐𝑐(2√3𝑎𝑎 ×4𝑎𝑎) structure is formed from the intercalation of alkali metals such as Na and Rb [41][42][43][44][45], similar to that found in the strained 1T-VSe2 studied here.…”
Section: Introductionmentioning
confidence: 66%
“…An alternative route to modify the CDW structure is intercalation that can change the electronic structure and induce strain. 1T-TaS2 is a case in point, as a new rectangular 𝑐𝑐(2√3𝑎𝑎 ×4𝑎𝑎) structure is formed from the intercalation of alkali metals such as Na and Rb [41][42][43][44][45], similar to that found in the strained 1T-VSe2 studied here.…”
Section: Introductionmentioning
confidence: 66%
“…LEED also shows very well charge density wave (CDW) formation in 1T-TaS 2 and 1T-TaSe 2 . Recently, the dependence of the CDW phases in these compounds on the function of intercalation [9,10] and surface nanostructuring [11,12] was studied in detail. On the contrary, no LEED studies of NbTe 2 or any other corrugated MX 2 compound were reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these two near-E F bands, a non-dispersive band marked by a horizontal green line, appears at ~ 0.5eV binding energy. It sits on the same energy level as that in Rb metal, where a density-of-state extreme exists [50,51]. It is reasonable to attribute such a flat band to an impurity band from the scattered Rb cluster on monolayer WSe 2 surface.…”
Section: Methodsmentioning
confidence: 86%